Ultrafine MnO(2) Nanowire Arrays Grown on Carbon Fibers for High-Performance Supercapacitors - Hu, Jiyu (Nanoscale Res Lett, 2016)
Large-area ultrafine MnO(2) nanowire arrays (NWA) directly grew on a carbon fiber (CF, used as a substrate) by a simple electrochemical method, forming three-dimensional (3D) hierarchical heterostructures of a CF@MnO(2) NWA composite. As an electrode for supercapacitors, the CF@MnO(2) NWA composite exhibits excellent electrochemical performances including high specific capacitance (321.3 F g(−1) at 1000 mA g(−1)) and good rate capability. Further, the overall capacitance retention is ~99.7 % capacitance after 3000 cycles. These outstanding electrochemical performances attribute to a large number of transport channels for the penetration of electrolyte and the transportation of ions and electrons of electrodes. The as-prepared CF@MnO(2) NWA composite may be a promising electrode material for high-performance supercapacitors.